A dynamic method for rolling transport network planning - Yun XIA; Ji’en SONG; Jie LI (Dianxin kexue)
Operators are facing double pressure of the rapid development of network and the drop of telecom charges.The construction of the transport network needs to consider the long-term development.The construction plan can not only meet the business needs of the near future,but also meet the future direction of business development.By analyzing the shortage of traditional rolling planning method,oriented by planning development goals,a dynamic rolling planning method of transport network was presented.The effect of the business developing trend to the network was transformed from the artificial fuzzy thinking into quantitative calculation method,to avoid investment waste caused by inconformity of network construction and business changes.